2019
DOI: 10.4178/epih.e2019049
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of barriers and motivators to physical activity in elderly adults in Iran and worldwide

Abstract: OBJECTIVES: This study was conducted to identify and characterize the barriers and motivations to physical activity (PA) for elderly adults in Iran and other countries.METHODS: We searched 6 databases (PubMed, Embase, Scopus, Web of Science, Magiran, and the Scientific Information Database) from 2000 to the November 2017, using “aged 60 and over,” “physical activity” or “exercise,” and “motivator” and “barrier” as keywords. Two reviewers independently performed the search, screening, and quality assessment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(99 citation statements)
references
References 46 publications
10
63
0
Order By: Relevance
“…This is in agreement with a recent review studying physical activity in the elderly, where the authors concluded that facilitators of and barriers to physical activity are more closely related to intrapersonal factors than to interpersonal and environmental factors (Yarmohammadi, Saadati, Ghaffari, & Ramezankhani, 2019). Contrary to this, an Australian population study with 2,194 adults found that the level and likelihood of participation in physical activity was strongly associated with various types of perceived barriers, but also with perceived benefits, social support, and environmental factors (Cerin, Leslie, Sugiyama, & Owen, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with a recent review studying physical activity in the elderly, where the authors concluded that facilitators of and barriers to physical activity are more closely related to intrapersonal factors than to interpersonal and environmental factors (Yarmohammadi, Saadati, Ghaffari, & Ramezankhani, 2019). Contrary to this, an Australian population study with 2,194 adults found that the level and likelihood of participation in physical activity was strongly associated with various types of perceived barriers, but also with perceived benefits, social support, and environmental factors (Cerin, Leslie, Sugiyama, & Owen, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Another limit was search terms are rather limited. Indeed, we did not include “Ageing” in our keywords because previous systematic and integrative reviews have not used this keyword [ 9 , 14 , 15 , 28 , 29 ]. However, we conducted an extensive literature search of several databases to identify as many publications as possible in order to include the most relevant ones.…”
Section: Discussionmentioning
confidence: 99%
“…With sedentary older people, the identification of reliable predictors allows healthcare providers to effectively structure interventions to promote changes in patterns of physical activity. Several reviews of the literature examining qualitative and quantitative studies on barriers and physical activity have identified conditions such as lack of time, lack of safe place and weather, environmental factors, physical problems and having no companions as mainly reported by sedentary older people [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. In contrast, there is a lack of information concerning the barriers for exercisers; attrition most commonly occurs within 6 months of exercise initiation, with approximately 50% of participants dropping out before realizing any health benefits [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…There were some barriers for elderly engaging in LTPA, such as health status, fear, and weather [ 14 ]. Poor health was reported as a barrier for elderly physical activity [ 15 , 16 ]. Fear form different origins was another reported barrier for elderly physical activity, including fear for exercising outside, fear for injury, fear for falling, and so on [ 15 ].…”
Section: Introductionmentioning
confidence: 99%